The multifaceted role of autophagy in skin autoimmune disorders: a guardian or culprit? - Lin, Yi; Wu, Xiuyi; Yang, Yiwen; Wu, Yue; Xiang, Leihong; Zhang, Chengfeng (Frontiers in Immunology, 2024)
Autophagy is a cellular process that functions to maintain intracellular homeostasis via the degradation and recycling of defective organelles or damaged proteins. This dynamic mechanism participates in various biological processes, including regulation of cellular differentiation, proliferation and survival, as well as modulation of inflammation and immune responses. Recent evidence has demonstrated the involvement of polymorphisms in autophagy-related genes in various skin autoimmune diseases. In addition, autophagy, along with autophagy-related proteins, also contributes to the homeostasis maintenance as well as immune regulation in the skin, associating autophagy with skin autoimmune disorders. This review aims to provide an overview of the multifaceted role of autophagy in skin autoimmune diseases and shed light on the potential of autophagy-targeting therapeutic strategies in dermatology.